Coordinating to avoid the catastrophe - Vitus Bühl; Robert C. Schmidt (ZBW - Leibniz Information Centre for Economics, 2020)
In the presence of a tipping point for dangerous climate damages, the cooperation problem of climate protection can be transformed into a coordination problem that is much easier to deal with (Barrett, 2013). This holds in particular if the amount of greenhouse gas emissions that triggers the catastrophe is precisely known, while the well-known free-rider problem re-appears if the location of the threshold is sufficiently uncertain. In this paper, we focus on the question how the non-signatories (outsiders of a climate agreement) coordinate to avoid the catastrophe, if the tipping point is known. In particular, in light of a multiplicity of equilibria in this coordination problem, the assumption that outsiders will always successfully coordinate to avoid the threshold, even if this is in their collective interest, seems overly optimistic. We analyze how the probability that the outsiders coordinate on an equilibrium in which the threshold is avoided, affects the incentives of countries to join the climate coalition. In some cases, there are multiple equilibria at the participation stage: an equilibrium with full participation, and an equilibrium in which a much smaller coalition forms - just large enough to achieve an outcome in which the catastrophe is avoided with positive probability.
Keywords: D62; F53; Q54; 330; tipping point; climate catastrophe; coordination game; international environmental agreement; climate cooperation